Online Information Systems: Who Should be Responsible for Preventing the Spread of Fake News? - Belhadjali, Moncef; Whaley, Gary L.; Abbasi, Sami M. (Archives of Business Research, 2017)
The dissemination of “Fake News” online has been deemed as a form of misinformation. This paper utilizes data from a survey of Internet users to compare their perceptions of who should take a great deal or a fair amount of responsibility in preventing the spread of fake news. The three main players concerned with taking additional responsibility in dealing with fake news are members of the public, government, and social networking sites. The users were defined by three demographic variables, and their perception of the amount of responsibility that the three players should have in preventing fake news stories from gaining momentum. The majority of respondents (91%) think that made up news stories hinder Americans. Also, the majority of Americans agree that all three players should be more responsible — public (76%), government (73%), and networking sites (76%). The results showed that there is a statistically significant gender difference; females are more likely than males to assign additional responsibility to all three players, regardless of ethnicity and party affiliation. In addition, the results showed that there is no statistically significant difference among Americans based on ethnicity and party affiliation. The one exception is that Democrats are more likely than Republicans to assign additional responsibility to social networking sites.